Tinjauan Literatur tentang Pemanfaatan Algoritma Greedy untuk Pencarian Jalur Terpendek - Dima, Javiardi; Hamzah, Moh. Syukron; Tallo, Clerinzia Gladista; Fallo, Diana Yanni Ariswati (Jurnal Kridatama Sains dan Teknologi, 2025)
The shortest path problem is a classical issue encountered in various applications such as geographic information systems (GIS), logistics management, transportation planning, and disaster evacuation routing. The Greedy Algorithm offers a simple solution approach that focuses on selecting the best local solution at each decision step, assuming that such local decisions will lead to a globally efficient solution. This research is a systematic literature review discussing the working principles, advantages, limitations, and real-world implementations of the Greedy Algorithm in solving shortest path problems. Based on the reviewed literature, the Greedy Algorithm performs efficiently for problems with low to medium complexity. However, its main limitation lies in its inability to guarantee globally optimal solutions in complex graphs with multiple alternative routes. Several empirical studies have demonstrated that the Greedy Algorithm is effectively utilized in tourist route mapping, parcel delivery systems, urban logistics management, adaptive traffic signal control, and disaster evacuation route planning. Therefore, the Greedy Algorithm remains a practical approach, particularly in systems that require fast computation with limited decision space.